Global investment risk management : protecting international portfolios against currency, interest rate, equity, and commodity risk - Zask, Ezra (New York : McGraw Hill, 2000)
The benchmark guide, written by 20 of today's hottest experts, that outlines a practical program for understanding and managing all aspects of international investment risk.
Includes bibliographical references and index.
rpm 19/08/16
Loans
Keywords: Investments, Foreign